2013
DOI: 10.1002/cctc.201300375
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Room‐Temperature Synthesis of [Al]MCM‐41 Materials for the Catalytic Conversion of Phenylglyoxal to Ethylmandelate

Abstract: Mesoporous [Al]MCM‐41 materials with nSi/nAl ratios of 15 to 50 suitable for the direct catalytic conversion of phenylglyoxal to ethylmandelate have been successfully synthesized at room temperature within 1 h. The surface areas and pore sizes of the obtained [Al]MCM‐41 materials are in the ranges of 1005–1246 m2 g−1 and 3.44–3.99 nm, respectively, for the different nSi/nAl ratios. For all [Al]MCM‐41 catalysts, most of the Al species were tetrahedrally coordinated with Si in the next coordination sphere of ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 60 publications
4
60
0
Order By: Relevance
“…Since SAx possess both lower acidity and surface areas compared to the De−Al‐HY zeolite, the excellent activity of the non‐porous SAx catalysts is attributed to the high external diffusion rates of reactant and product compared to the constrained internal diffusion occurring in the cages and narrow channels of zeolites. The absence of pore diffusion limitations in the SAx catalysts facilitates high TOFs similar to those reported earlier …”
Section: Resultssupporting
confidence: 83%
“…Since SAx possess both lower acidity and surface areas compared to the De−Al‐HY zeolite, the excellent activity of the non‐porous SAx catalysts is attributed to the high external diffusion rates of reactant and product compared to the constrained internal diffusion occurring in the cages and narrow channels of zeolites. The absence of pore diffusion limitations in the SAx catalysts facilitates high TOFs similar to those reported earlier …”
Section: Resultssupporting
confidence: 83%
“…Experiments using probe molecules have confirmed the role of flexible or PBS Si-OH···Al IV coordination as BAS in ASA569162021. Similar methods using ammonia probe molecules were applied here to demonstrate the acidity of the Si-OH···Al V coordination observed in dehydrated SA/10 and SA/50 (ref.…”
Section: Resultsmentioning
confidence: 55%
“…However, previous works have shown that the Al atoms with neighbouring SiOH groups (Fig. 1b,c) do not produce such a shift of the 1 H MAS signal of these groups569162021. Supplementary Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These two kinds of supports have amazing feature. Mesoporous materials like MCM‐41 and SBA‐16 have specific properties such as large BET surface area, great thermal stability, good catalytic performance, regularly arranged pore structure, tunable and accessible pores, controlled morphology, non‐toxicity, and low preparation cost …”
Section: Introductionmentioning
confidence: 99%